"'Cause Everybody Likes to Be Treated Good": Perceptions of Procedural Justice Among Mental Health Court Participants. (February 2013) - Canada, Kelli E.; Watson, Amy C.
There is mounting evidence that mental health courts (MHCs) reduce criminal recidivism and increase use of mental health services. Although not yet empirically tested, procedural justice has been proposed as one potential mechanism that promotes change and improves outcomes for MHC participants. In this article, we investigate MHC participants' perceptions of procedural justice in interactions with MHC staff as well as the role of procedural justice in participants' MHC program experiences. Participants from two MHC programs were invited to complete quantitative measures and a semistructured interview about their MHC experiences and perceptions of procedural justice. Univariate and bivariate analyses and qualitative analysis were used to examine the data. Findings indicate that MHC participants perceive a moderate level of procedural justice in interactions with MHC team members. However, perceptions of procedural justice are complex, involve multiple actions and inaction, and are affected by all members of the MHC team, not just the judge. Although scores on quantitative measures of procedural justice do not differ by court, participant perceptions discussed in semistructured interviews do vary. Implications for practice, policy, and research are discussed.